PT. BAI (Bintan Alumina Indonesia) as Juggernaut in the People of Bintan Regency - Safitri Ramayani; Nanik Rahmawati; Rahma Syafitri (Social Issues Quarterly, 2023)
This study examines the public's perception of the impact of PT. BAI's existence in Bintan Regency. The research aims to investigate the changes that PT. BAI brings to people's lives and the impact of these changes on the surrounding environment. The research uses a qualitative approach with descriptive methods, including observations, interviews, and documentation. In-depth structured face-to-face interviews were conducted with informants selected through purposive sampling. The study employs Anthony Giddens' Juggernaut Modernity Theory, which describes how a large machine can control or destroy in modernity. The study found that the community views PT. BAI's presence positively due to its ability to create employment opportunities and improve people's welfare, but negatively due to PT. BAI's land tenure practices. PT. BAI is both a Juggernaut that benefits the community by providing jobs and reducing unemployment, and a Juggernaut that cannot be controlled with regard to land tenure. The study concludes that PT. BAI's existence brings positive impacts such as reducing unemployment and increasing people's welfare, as well as negative impacts on land tenure.